Teaching games for understanding : Theory, research and practice - Griffin, Linda L.; Butler, Joy I. (United States : Human Kinetics, 2005)
Presents a comprehensive guide for teachers and coaches that details the history, theory, research, and practice of the Teaching Games for Understanding model, and how to incorporate it in both elementary and secondary curriculum.
Includes bibliographical references and index.
Keywords: Sports--Study and teaching; Physical education and training--Study and teaching; Student-centered learning